Executive board and supervisory board members in Germany's large corporations remain predominantly male - Elke Holst; Anja Kirsch (DIW Economic Bulletin, 2014)
The executive boards of large corporations in Germany continue to be in men's hands: at the close of 2014, a good five percent of executive board members at the top 200 companies in Germany were women. This is equivalent to an increase of one percentage point over 2013, which is evidence of the rather sluggish development in this area. DAX 30 companies recorded the largest proportion of female board members at a good seven percent, while the lowest share was recorded for MDAX companies (less than three percent). The representation of women on supervisory boards was better: at the end of 2014, a good 18 percent of board members were women in the top 200 companies; DAX 30 companies displayed above-average results for female board members at just below 25 percent. At a little under 14 percent, SDAX companies displayed not only the lowest percentage of women, but also the lowest increase over 2013 (0.6 percentage points). Both on executive and supervisory boards, female chairpersons remain the exception. Following the law passed by the federal government cabinet last year on equality for women and men in managerial positions, both at private companies and in the civil service, female representation, at least on supervisory boards, is likely to improve. The gender quota introduced in this legislation will come into effect on January 1, 2016. Companies with government-owned shares will also be affected by the quota regulation. Here, female representation on the supervisory boards and executive boards at the end of 2014 was just under 24 and just under 15 percent, respectively.
Keywords: D22; J16; J59; J78; L21; L32; M14; M51; 330; board diversity; board composition; female directors; corporate boards; women CEOs; gender equality; management; listed companies; private companies; public companies; women's quotas; gender quotas